Early-Onset Molecular Derangements in the Olfactory Bulb of Tg2576 Mice: Novel Insights Into the Stress-Responsive Olfactory Kinase Dynamics in Alzheimer’s Disease - Lachen-Montes, Mercedes; González-Morales, Andrea; Palomino, Maialen; Ausin, Karina; Gómez-Ochoa, Marta; Zelaya, María Victoria; Ferrer, Isidro; Pérez-Mediavilla, Alberto; Fernández-Irigoyen, Joaquín; Santamaría, Enrique (Frontiers in Aging Neuroscience, 2019)
The olfactory bulb (OB) is the first processing station in the olfactory pathway. Despite smell impairment, which is considered an early event in Alzheimer’s disease (AD), little is known about the initial molecular disturbances that accompany the AD development at olfactory level. We have interrogated the time-dependent OB molecular landscape in Tg2576 AD mice prior to the appearance of neuropathological amyloid plaques (2-, and 6-month-old), using combinatorial omics analysis. The metabolic modulation induced by overproduction of human mutated amyloid precursor protein (APP) clearly differs between both time points. Besides the progressive perturbation of the APP interactome, functional network analysis unveiled an inverse regulation of downstream extracellular signal-regulated kinase (ERK1/2), and p38 mitogen-activated protein kinase (MAPK) routes in 2-month-old Tg2576 mice with respect to wild-type (WT) mice. In contrast, Akt and MAPK kinase 4 (SEK1)/ stress-activated protein kinase (SAPK) axis were parallel activated in the OB of 6-months-old-Tg2576 mice. Furthermore, a survival kinome profiling performed during the aging process (2-, 6-, and 18-month-old) revealed that olfactory APP overexpression leads to changes in the activation dynamics of protein kinase A (PKA), and SEK1/MKK4-SAPK/JNK between 6 and 18 months of age, when memory deficits appear and AD pathology is well established in transgenic mice. Interestingly, both olfactory pathways were differentially activated in a stage-dependent manner in human sporadic AD subjects with different neuropathological grading. Taken together, our data reflect the early impact of mutated APP on the OB molecular homeostasis, highlighting the progressive modulation of specific signaling pathways during the olfactory amyloidogenic pathology.